Building and Sustaining National ICT/Education Agencies : Lessons from Malaysia - Lee, Molly N.N. (World Bank, Washington, DC, 2017)
Malaysia, like many countries in the region, has invested heavily in the use of ICT in schools since 1999. Unlike many other countries, Malaysia does not rely on a single specialized agency or a particular division of the Ministry of Education to implement its ICT in education programmes. Instead, the Malaysian government rolled out a nation-wide initiative known as the 'Smart School Initiative', which is based on strategic public-private partnerships involving various stakeholders including ministry, industry, and community. This case study examines how the Malaysian Smart School Initiative (MSSI) was developed and implemented in its initial years. The study demonstrates that the MSSI was the result of a deliberate, holistic approach to incorporate the use of ICT in Malaysian schools. The MSSI involved not only the use of ICT in the teaching and learning process, but also in the management and administrators and technicians in using ICT effectively in their daily practices.